DIDACTIC DEVELOPMENT DESIGN OF THE OBJECT. PRINCIPLES AND TOOLS OF DESIGN IN ENGLISH HISTORIOGRAPHY PROBLEMS - Тютькіна, Ірина (SWorldJournal, 2023)
Didactic design objects are a relevant group of design objects. The main characteristic of which is related to various practices of learning and gaining experience, which often leads to a rethinking of the usual material stereotypes. It is the developing